Saccharomyces paradoxus Transcriptional Alterations in Cells of Distinct Phenotype and Viral dsRNA Content - Bazilė Ravoitytė; Juliana Lukša; Vyacheslav Yurchenko; Saulius Serva; Elena Servienė (Microorganisms, 2020)
Killer yeasts are attractive antifungal agents with great potential applications in the food industry. Natural Saccharomyces paradoxus isolates provide new dsRNA-based killer systems available for investigation. The presence of viral dsRNA may alter transcriptional profile of S. paradoxus. To test this possibility, a high-throughput RNA sequencing was employed to compare the transcriptomes of S. paradoxus AML 15-66 K66 killer strains after curing them of either M-66 alone or both M-66 and L-A-66 dsRNA viruses. The S. paradoxus cells cured of viral dsRNA(s) showed respiration deficient or altered sporulation patterns. We have identified numerous changes in the transcription profile of genes including those linked to ribosomes and amino acid biosynthesis, as well as mitochondrial function. Our work advance studies of transcriptional adaptations of Saccharomyces spp. induced by changes in phenotype and set of dsRNA viruses, reported for the first time.